ACCESUL DESCHIS – UN NOU MODEL DE ACCES LA INFORMAŢIE ŞI CUNOAŞTERE - ŢURCAN,Conf. univ. dr., Facultatea de Jurnalism şi Ştiinţe ale Comunicării, USM, Nelly (BIBLIOPOLIS, 2020)
In the Information and Knowledge Society the free information circulation is essential for the realisation of the universal access to the information and knowledge. The Open Access was sustained by several international associations of researchers, publishers, librarians, and the Association of the Librarians of the Republic of Moldova (ABRM). The author, dr. Nelly Turcan, analyses the strategies and the models, that ensure the Open Access to the scientifi c literature. The paper highlights the potential benefi ts of the Open Access and detects groups (authors, readers, teachers and students, libraries, universities, publishers, governments) that OA serves and the benefi ts for each group. The Open Access serves citizens, which gives access to recent researches and to researches already funded from public money and taxes. The Open Access helps indirectly the citizens off ering the information assistance to the researchers and other people using the study’s results.